2008
DOI: 10.1016/j.rmed.2007.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bronchoalveolar lavage fluid from ARDS patients with regard to apoptosis

Abstract: Among the mediators in BAL fluid from ARDS patients, G-CSF had the most significant prognostic implications, and the sFas and TRAIL levels were correlated with clinical severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 38 publications
3
40
0
1
Order By: Relevance
“…Apoptosis of epithelial and endothelial cells has been observed in the lung of ARDS patients [40]. Apoptosis mediators are also increased in the BAL (bronchoalveolar lavage) fluid of ARDS patients [41]. A delayed apoptosis of intra-alveolar neutrophils with a concomitant increased apoptosis of alveolar epithelium increases the severity of lung injury [41].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of epithelial and endothelial cells has been observed in the lung of ARDS patients [40]. Apoptosis mediators are also increased in the BAL (bronchoalveolar lavage) fluid of ARDS patients [41]. A delayed apoptosis of intra-alveolar neutrophils with a concomitant increased apoptosis of alveolar epithelium increases the severity of lung injury [41].…”
Section: Discussionmentioning
confidence: 99%
“…Various stimuli may evoke complex “adaptive” responses to pathogens by neutrophils, by either decreasing (tolerance) or increasing (priming) activation [17,18]. Neutrophil function appears dysregulated in ARDS [19–26], and the potential exists that a beneficial adaptation to one microbe may place the host at a disadvantage against other infectious agents or inflammatory insults.…”
Section: Introductionmentioning
confidence: 99%
“…(Beheshti et al, 2006;Emmler et al, 2007;Kuwano, 2008;Perl et al, 2008). In all of these cases, Fas and FasL are upregulated in the airway epithelial cells and are thought to contribute to cellular apoptosis (MatuteBello et al, 1999;Albertine et al, 2002;Hagimoto et al, 2002;Lee et al, 2008). The severity of the infection in septic ALI was highly correlated with the Fas-FasL system (Albertine et al, 2002); furthermore, acute respiratory distress syndrome nonsurvivors were shown to have markedly higher levels of FasL than survivors (Matute-Bello et al, 1999).…”
Section: Discussionmentioning
confidence: 99%